Pengaruh Wisatawan, Transportasi, dan Fasilitas Terhadap Pendapatan Pelaku UMKM Periwisata di Kabupaten Tana Toraja - Angela Haspin Oktiani Tudang; Jemi Pabisangan Tahirs; Mince Batara (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Angela Haspin Oktiani Tudang (2023). This study aims to determine the effect of tourists, transportation and facilities on the income of tourism MSMEs in Tana Toraja Regency. This study used a questionnaire that was distributed to tourists and tourism MSMEs in Tana Toraja district. The data analysis technique used is descriptive statistical test, validity and reliability test, classic assumption test, multiple regression analysis and hypothesis testing with SPSS version 23. The results of the study show that partially tourists, transportation and facilities have a significant influence on the income of MSME actors. Variable tourist, transportation, facilities and income of MSME actors show values that have a close relationship between variables. So it can be concluded that tourists, transportation and facilities affect the income of MSME actors.